A especialização produtiva do setor sucroenergético do município de Santa Vitória/MG - Borges, Matheus Alfaiate (2023)
The objective of this study is to understand the process of productive expansion of the sugar-energy sector in the municipality of Santa Vitória/MG, especially in recognition as a specialized municipality. To carry out this research, the methodological referrals were separated into stages, namely: (a) bibliographical survey, (b) collection of census data, (c) field work, (d) tabulation of data and production of cartographic products, and to put an end, (e) the organization and final writing of the study. The justification was highlighted by data elucidated from the Municipal Agricultural Production (2022) in which it demonstrated that from the year 2000 the harvested area of sugarcane in the municipality of Santa Vitória/MG increased from 40 hectares to 36,000 (hectares) in 2020, corresponding to a percentage of 89.66 of the total area, modeling the specialization of grass as the main agricultural crop in the municipality. In this sense, it is considered that there is a concentration of sugar-energy activities in the municipality of Santa Vitória/MG, which is revealed not only by the occupation of sugarcane in almost 90% of the arable area, but also because it is the main activity economy, the one that employs the most in the whole municipality, that is, only for the manufacture of sugar and alcohol, the job occupation is 38%, a number that is very expressive, even more when compared with the second and third placed, being the second public administration (occupying 21%) and the third cattle raising with about 7.6%. It is worth mentioning that the concentration of sugar-energy activities is something that implies situations that impact the environment, whether in the deforestation of trees or even in the contamination of areas with vinasse and other pesticides that are released in the cultivation of sugarcane, so it is something that needs to be reviewed, mainly by the public authorities.